Shorter Notices (The Muslim world, 1962)
Inside the Arab Mind. By Fahim I. The Arab Nation - Paths and Obstacles to Fulfillment. By William Sands. The Arab Middle East and Muslim Africa Edited by Tibor Kerekes. Abr-Nahrain. An Annual, edited by John Bowman. France and Algeria: Complementary Enemies. By Germaine Tillion. The History of Modern Iran - an Interpretation. By Joseph M. Upton. Run Softly Demerara. By Zahra Freeth. L’Influence Religieuse sur le Droit Constitutionel de l'Iran. By Manoutchehr Khodayar Mohebbi. A Selected and Annotated Bibliography of Economic Literature on the Arabic Speaking Countries of the Middle East. 1959 Supplement. Middle East Economic Papers 1959.